Endosomal trafficking protein TBC-2 is required for the longevity of long-lived mitochondrial mutants - Traa, Annika; Shields, Hazel; AlOkda, Abdelrahman; Rudich, Zenith D.; Ko, Bokang; Van Raamsdonk, Jeremy M. (Frontiers in Aging, 2023)
Mutations that result in a mild impairment of mitochondrial function can extend longevity. Previous studies have shown that the increase in lifespan is dependent on stress responsive transcription factors, including DAF-16/FOXO, which exhibits increased nuclear localization in long-lived mitochondrial mutants. We recently found that the localization of DAF-16 within the cell is dependent on the endosomal trafficking protein TBC-2. Based on the important role of DAF-16 in both longevity and resistance to stress, we examined the effect of disrupting tbc-2 on lifespan and stress resistance in the long-lived mitochondrial mutants nuo-6 and isp-1 in Caenorhabditis elegans. Loss of tbc-2 markedly reduced the long lifespans of both mitochondrial mutants. Disruption of tbc-2 also decreased resistance to chronic oxidative stress in nuo-6 and isp-1 mutants but had little or no detrimental effect on resistance to other stressors. In contrast, tbc-2 inhibition had no effect on oxidative stress resistance or lifespan in isp-1 worms when DAF-16 is absent, suggesting that the effect of tbc-2 on mitochondrial mutant lifespan may be mediated by mislocalization of DAF-16. However, this result is complicated by the fact that deletion of daf-16 markedly decreases both phenotypes in isp-1 worms, which could result in a floor effect. In exploring the contribution of DAF-16 further, we found that disruption of tbc-2 did not affect the nuclear localization of DAF-16 in isp-1 worms or prevent the upregulation of DAF-16 target genes in the long-lived mitochondrial mutants. This suggests the possibility that the effect of tbc-2 on lifespan and stress resistance in the long-lived mitochondrial mutants is at least partially independent of its effects on DAF-16 localization. Overall, this work demonstrates the importance of endosomal trafficking for the extended longevity and enhanced stress resistance resulting from mild impairment of mitochondrial function.